111k views
2 votes
Math factor and solve .

User Fxlemire
by
4.7k points

1 Answer

4 votes

Answer:

x = -1 and x = 2/3

Explanation:

The equation given is a quadratic equation.

Therefore, to solve for x we use the quadratic formula.

The quadratic formula says that if we have an equation of the form


ax^2+bx+c=0

Then the values of x (solutions) are given by


x=(-b\pm√(b^2-4ac))/(2a)

Now in our case, the equation we have is


3x^2+x-2=0

which tells us that a = 3, b = 1, and c = -2; therefore, quadratic formula gives


x=(-1\pm√((1)^2-4(3)(-2)))/(2(3))

which we simplify a bit to get


x=(-1\pm√(1+24))/(6)
\Rightarrow x=(-1\pm5)/(6)

which gives us two solutions:


x=(-1-5)/(6)=-1
x=(-1+5)/(6)=(2)/(3)

Hence, the two solutions to the quadratic equation are x = -1 and x = 2/3.

User Will Goring
by
4.7k points